2019
DOI: 10.1186/s12974-019-1448-x
|View full text |Cite
|
Sign up to set email alerts
|

CD55 upregulation in astrocytes by statins as potential therapy for AQP4-IgG seropositive neuromyelitis optica

Abstract: Background Neuromyelitis optica spectrum disorder (herein called NMO) is an inflammatory demyelinating disease that can be initiated by binding of immunoglobulin G autoantibodies (AQP4-IgG) to aquaporin-4 on astrocytes, causing complement-dependent cytotoxicity (CDC) and downstream inflammation. The increased NMO pathology in rodents deficient in complement regulator protein CD59 following passive transfer of AQP4-IgG has suggested the potential therapeutic utility of increasing the expression of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 58 publications
1
11
0
1
Order By: Relevance
“…Our understanding of the role of complement regulators represents a great research opportunity. Recently, among various other statins, atorvastatin upregulated CD55 and reduced pathology in an experimental mouse model . The site at which the therapy induces the upregulation of complement regulatory proteins in seropositive patients with NMOSD warrants further investigation.…”
Section: Cellular Expression and Tissue Distribution Of Aqp4mentioning
confidence: 99%
See 1 more Smart Citation
“…Our understanding of the role of complement regulators represents a great research opportunity. Recently, among various other statins, atorvastatin upregulated CD55 and reduced pathology in an experimental mouse model . The site at which the therapy induces the upregulation of complement regulatory proteins in seropositive patients with NMOSD warrants further investigation.…”
Section: Cellular Expression and Tissue Distribution Of Aqp4mentioning
confidence: 99%
“…Additionally, the discovery of the requirement for complement in the formation of lesions suggests that complement inhibitors, such as the C1 inhibitor, may be an effective approach to limit CNS injury in patients with NMO. Similarly, the upregulation of complement regulators, such as CD55, by statins may provide a substantial clinical benefit . The therapeutic monoclonal IgG eculizumab that neutralizes the complement protein C5 appears to be well tolerated, reduces the frequency of attack and improves neurological disability when used to treat intractable cases .…”
Section: Future Directionsmentioning
confidence: 99%
“…Lastly, all included patients were treated with aspirin for at least a week before Mediators of Inflammation inclusion and nearly all used statins. Aspirin has been shown to inhibit complement activation and NET formation [50][51][52], and statin use has been shown to both stimulate and inhibit NET formation [53][54][55][56]; thus, this medication may have influenced the observed associations in our cohort.…”
Section: Mediators Of Inflammationmentioning
confidence: 99%
“…The results also implicate complement regulator proteins as new targets in NMO in which their upregulation is predicted to protect against complement‐induced injury. Motivated by these observations, drug screening identified statins as transcriptional enhancers of CD55 expression in astrocyte cell culture models and in mice, and reported that oral atorvastatin significantly reduced NMO pathology in a passive transfer mouse model of NMO .…”
Section: Scientific Advances Utilizing Nmo Animal Modelsmentioning
confidence: 99%
“…These data offered proof‐of‐concept for the potential utility of a remyelinating approach in NMO. Animal models of NMO have also been used to demonstrate efficacy of C1q‐targeted and Fc hexamer complement therapeutics, aquaporumab antibody and small molecule blockers of AQP4‐IgG/AQP4 binding, IgG‐inactivating enzymes , IVIG and a statin upregulator of CD55 , as well as the lack of efficacy of various proposed therapeutics including C1‐esterase inhibitor .…”
Section: Scientific Advances Utilizing Nmo Animal Modelsmentioning
confidence: 99%